The Implementation of a Center-Based Learning Model in Early Childhood Education at TK Negeri Pembina Pacitan - Marianti Titi Lestari; Septyana Tentiasih (Manunggal Halim Jaya, 2026)
This study aims to describe the implementation of the center-based learning model in early childhood education, its implications for child development, and to identify its strengths and challenges at TK Negeri Pembina Pacitan. This research uses a qualitative approach with a field research method. Data was collected through observation, interviews, and documentation. The results show that the implementation of the center-based learning model has been carried out quite well through planning, learning environment arrangement, core activities in learning centers, and closing activities. The model positively impacts children’s development, including cognitive, social-emotional, language, and motor aspects in a holistic way through play-based learning. In addition, the model increases children’s activeness, independence, and enthusiasm. However, several challenges were found, such as limited facilities, time management issues, and varying teacher competencies in managing learning centers.